2020
DOI: 10.1016/s2665-9913(20)30237-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of abatacept in early diffuse cutaneous systemic sclerosis (ASSET): open-label extension of a phase 2, double-blind randomised trial

Abstract: BackgroundWe recently reported that abatacept was well tolerated with potential efficacy for early diffuse cutaneous systemic sclerosis (dcSSc) in a phase II placebo-controlled randomized trial. We report here the results of the six-month open-label extension (OLE) period. MethodsThis was a double-blind, randomized controlled trial with OLE conducted at 22 centers in the US, Canada, and the UK (clinicaltrials.gov NCT 02161406). Participants with dcSSc of < 3 years duration from first non-Raynaud symptom were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In a phase II trial, abatacept showed a nonsignificant reduction in FVC decline at 12 months (least squares mean FVC% 2.79% [95%CI −0.69, 6.27], favoring abatacept compared to placebo) (64). A similar trend was observed in the open-label extension at month 18 (65). In an open-label trial comparing rituximab to CYC, mean ± SD FVC% improved from 61.30 ± 11.28% at baseline to 67.52 ± 13.59% at 6 months in the rituximab arm, but declined from 59.25 ± 12.96% to 58.06 ± 11.23% in the CYC arm, with a mean difference in FVC% at 6 months of 9.46 (95% CI 3.01, 15.90) (P = 0.003) (66).…”
Section: Clinical Evidence For the Management Of Ssc-ild Based On Phase II And Iii Trialsmentioning
confidence: 61%
“…In a phase II trial, abatacept showed a nonsignificant reduction in FVC decline at 12 months (least squares mean FVC% 2.79% [95%CI −0.69, 6.27], favoring abatacept compared to placebo) (64). A similar trend was observed in the open-label extension at month 18 (65). In an open-label trial comparing rituximab to CYC, mean ± SD FVC% improved from 61.30 ± 11.28% at baseline to 67.52 ± 13.59% at 6 months in the rituximab arm, but declined from 59.25 ± 12.96% to 58.06 ± 11.23% in the CYC arm, with a mean difference in FVC% at 6 months of 9.46 (95% CI 3.01, 15.90) (P = 0.003) (66).…”
Section: Clinical Evidence For the Management Of Ssc-ild Based On Phase II And Iii Trialsmentioning
confidence: 61%
“…Over the 6-month open-label extension, no new safety signals emerged. Moreover, clinically meaningful improvement in the mRSS was observed in both the abatacept and PBO groups when patients transitioned to abatacept supporting further studies of abatacept in dcSSc [ 43 ].…”
Section: Resultsmentioning
confidence: 57%
“…In SLE and other inflammatory connective tissue diseases, Abatacept has shown efficacy in animal models, but generally failed in clinical studies ( 96 , 97 ). Since the first casuistic report of Abatacepts efficacy in SSc, a phase II study has supported CTLA-4s possible role in the treatment of this disease ( 98 , 99 ). Evidence on CTLA-4’s role in initiating connective tissue diseases remains to be fully elucidated, and most evidence is only on the genetic polymorphisms of CTLA-4 being associated with an increased risk of connective tissue diseases ( 100 ).…”
Section: Ctla-4mentioning
confidence: 96%